Implementing Data-Based Planning in Elementary School: A Case Study at SD Negeri 2 Pamotan - Sudadi, Sudadi; Rasiman, Rasiman; Soedjono, Soedjono (Journal of Educational Sciences, 2025)
Data-Based Planning is a national education policy designed to improve school quality through evidence-based decision-making, yet its optimal implementation remains a challenge in many schools due to limited data literacy among principals. This study examines the implementation of PBD at SD Negeri 2 Pamotan, Rembang Regency, focusing on the principal’s role, challenges faced, and strategies to optimize the process. Employing a qualitative descriptive approach, data were gathered through interviews, observations, and document analysis involving school leaders and teachers. Findings reveal that the principal carried out all stages of the PBD cycle identifying challenges using the Education Report Card, reflecting on performance, and revising programs based on data while fostering collaborative planning, empowering teachers, and supervising program execution in line with school needs. Despite constraints in data management skills and human resources, the school effectively integrated data into decision-making, achieving notable improvements in literacy, instructional quality, and student character development. The study concludes that successful PBD implementation requires both reliable data access and the principal’s leadership capacity to guide data-informed planning and drive continuous improvement.